2010
DOI: 10.3727/096368910x492616
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of Olfactory Ensheathing Cell Growth and Migration on Electrospun Silk Fibroin Scaffolds

Abstract: Transplantation of olfactory ensheathing cells (OECs) is a potential treatment for spinal cord injury (SCI). However, this process lacks extracellular matrix guiding cell growth, tissue morphogenesis, and remodeling. In order to solve this problem, we fabricated silk fibroin scaffolds (SFS) with different fiber diameters by electrospinning. The behaviors of OECs on 300 and 1800 nm SFS were studied by analyzing cell morphological feature, distribution, and proliferation. The results showed the 300 nm SFS with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…The cell transmembrane proteins responsible for the cytoskeleton development and organization are sensitive to the regularly alternating pattern at the nanometer scale. A similar effect was reported in (35), where the authors found a dependence of cell shape and alignment on the dimensions of electrospun silk fibroin fibres.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The cell transmembrane proteins responsible for the cytoskeleton development and organization are sensitive to the regularly alternating pattern at the nanometer scale. A similar effect was reported in (35), where the authors found a dependence of cell shape and alignment on the dimensions of electrospun silk fibroin fibres.…”
Section: Discussionsupporting
confidence: 63%
“…To facilitate this process of cell growth and guidance many researchers have started to develop biohybrids where OECs are seeded previously on different biomaterials (35)(36)(37)(38)(39). These kinds of structures have been produced from natural biomaterials such as alginate (40), collagen (41,42) and chitosan, synthetic polymers such as polyethylene glycol (43) , polylactic acid (44) or poly--caprolactone (39,43), and composite biomaterials (45).…”
Section: Introductionmentioning
confidence: 99%
“…5F). proliferation has recently been carried out on over glass surfaces with artificially generated gradients (Yan et al, 2003;Cao et al, 2006;Vukovic et al, 2009;Huang et al, 2011), in collagen scaffolds (Wang et al, 2006;Mollers et al, 2009), in nanofibers (Shen et al, 2010) and in biomaterial-coated substrates (Martin-Lopez et al, 2010b;Martin-Lopez et al, 2010a).…”
mentioning
confidence: 99%
“…Wang et al discovered that crossed fibers in the aligned fiber scaffold could be detrimental in axonal outgrowth, and that cell attachment and growth could depend on fiber density [95]. In addition, the diameter of electrospun fibers could also influence cell attachment, proliferation and migration [281]. The electrospinning process can be readily used to produce polymer fibers on the nanometer scale.…”
Section: Aligned Electrospun Polymer Fiber Scaffolds Guide Cellsmentioning
confidence: 99%